2020
DOI: 10.1093/cid/ciaa1692
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the 405 and the 5: Geographic Variations and Factors Associated With Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Positivity Rates in Los Angeles County

Abstract: Objectives To highlight geographic differences and the socio-structural determinants of SARS-CoV-2 test positivity within Los Angeles County (LAC). Methods A geographic information system was used to integrate, map, and analyze SARS-CoV-2 testing data reported by LAC DPH, and data from the American Community Survey. Structural determinants included race/ethnicity, poverty, insurance status, education, population and household… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 14 publications
3
37
0
1
Order By: Relevance
“…Younger populations should be included among targets in public health interventions. Disparities in COVID-19 mortality may be driven by a variety of factors, including complex interaction between social and structural determinates of health, barriers to accessing care, higher prevalence of underlying co-morbidities associated with more severe COVID-19 disease and adverse outcomes, and differential exposure to virus due to working and living conditions [ 24 , [29] , [30] , [31] , [32] , [33] , [34] ]—which maybe different and interact differently among the different groups (race/ethnicity and ethnicity/nativity) and subgroups (age-race/ethnicity and age-ethnicity/nativity groups) examined here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Younger populations should be included among targets in public health interventions. Disparities in COVID-19 mortality may be driven by a variety of factors, including complex interaction between social and structural determinates of health, barriers to accessing care, higher prevalence of underlying co-morbidities associated with more severe COVID-19 disease and adverse outcomes, and differential exposure to virus due to working and living conditions [ 24 , [29] , [30] , [31] , [32] , [33] , [34] ]—which maybe different and interact differently among the different groups (race/ethnicity and ethnicity/nativity) and subgroups (age-race/ethnicity and age-ethnicity/nativity groups) examined here.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported differential COVID-19 impacts across racial/ethnic groups including for incidence [ 1 , 35 ], severity [ [4] , [5] , [6] , [8] , [9] , [10] ], death [ 12 , 13 , 27 ], however few studies have examined outcomes by nativity [36] . Ecologic studies have reported COVID-19 incidence rates to be positively associated with higher population percentage Black [ 14 , 26 , 37 ], Hispanic/Latino [ 15 , 26 , 34 , 37 ], or foreign-born [ 26 , 37 ]. In a Massachusetts study the association for Latino population percentage was attenuated after accounting for percent foreign-born noncitizens living in a community, mean household size, and share of food service workers (all which were also positively associated with incidence) [37] .…”
Section: Discussionmentioning
confidence: 99%
“…To be sure, we confirmed the quantitative importance of multi-generational household prevalence in a cross-sectional regression analysis that included other measures of poverty ( INC22 , SNAP ) as well as the proportion of households with high-risk workers ( OCCUP ) (Table 2 ). Still, one might posit that the critical underlying variable is the proportion of Spanish-speaking households with uninsured members (Vijayan et al 2020 ; Weng et al 2020 ). One might similarly contend that our variable MULTI , which relied on the presence of at least one younger adult (aged 18–34) and another older adult (aged 45 or more) in the household, was no better an indicator of multi-generational transmission risk than, say, the number of persons per bathroom in the household.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital admission rates have been studied as an alternative to confirmed case incidence (Harris, 2020b , 2020g ), but such an endpoint would also depend on case severity. The test positivity rate—the proportion of positive tests among all persons tested—has been employed as an endpoint in cross-sectional studies (Cotti et al 2020 ; Vijayan et al 2020 ). Adaptation of this endpoint to a dynamic epidemic model is problematic, however, as the number of individuals tested is endogenous and must be modeled as well (Bhaduri et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation